Adaptation Strategies for Climate- Resistance Aquaculture: Insight from farmed fish - Amogha K. R; Shivani D. Gowda; Ganapathi Naik. M. (International Journal of Marine Life, 2024)
As global climate change threatens food security, particularly regarding the vital protein source of fish, innovative strategies such as climate smart aquaculture emerge as critical solutions. This approach emphasizes the cultivation of climate-resilient fish species capable of thriving in changing environmental conditions. By integrating air-breathing species like the Pangasius catfish and the Giant Snakehead, aquaculture industries can bolster local economies while mitigating environmental risks. However, successful implementation requires careful consideration of both positive and negative tradeoffs. Challenges such as temperature shifts, ocean acidification, and water scarcity demand adaptive techniques like biofloc technology to maintain water quality and enhance sustainability. Furthermore, indigenous species cultivation not only supports local communities but also safeguards ecosystems. The development of sustainable aquaculture practices suited to regional needs relies heavily on the collaborative efforts of academic institutions, research organizations, and local stakeholders. Ensuring responsible and inclusive growth in the aquaculture industry requires a thorough understanding of the socio-economic impacts of climate change on aquaculture communities. Overall, climate-resilient aquaculture represents a multifaceted approach to addressing global food security challenges amidst a changing climate landscape. In addition to species diversification, the abstract calls for a comprehensive research agenda focusing on cultivation techniques for new species and the socio-economic ramifications of climate change on aquaculture communities. Collaborative initiatives such as those undertaken by Aqua Fish partners across various institutions underscore the importance of interdisciplinary cooperation in developing sustainable aquaculture practices. The adoption of resilient practices like biofloc technology not only enhances water quality but also promotes ecological balance within aquaculture systems. Moreover, the cultivation of indigenous species not only fosters food security but also preserves cultural heritage and biodiversity. By addressing these multifaceted challenges through innovative approaches and collaborative efforts, climate-resilient aquaculture can play a pivotal role in ensuring food security for the world's growing population amidst changing environmental conditions.
Keywords: Climate; Pangasius Catfish; Protopterus antiepics; Recirculation aquaculture; aquaculture